The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/19443994.2014.884684
|View full text |Cite
|
Sign up to set email alerts
|

The optimization of chlorine dose in water treatment process in order to reduce the formation of disinfection by-products

Abstract: A B S T R A C TThe main threat to human health is associated with organic compounds, which are found in the natural water ecosystem. The law relating to drinking water quality protects consumers' health. Thus, the need to remove disinfection by-products (DBP) precursors requires the application of high-efficient water treatment processes. Usually, chlorine is used to disinfection, and then, haloforms are generated. Well-calibrated model, estimating the concentration of DBP in treated water, can be a useful too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Chlorine is an oxidizing agent that reacts rapidly with organic and inorganic matter present in water (WHO, 1996). Unfortunately, natural organic matter (NOM) in water reacts with chlorine to form THMs as disinfection byproducts (D-BPs) (Zimoch, 2014). However, the presence of THMs in chlorinated drinking water and their lifetime exposure on humans have raised a great concern due to its carcinogenicity and recognition as potential risk to human health (Zimoch, 2010).These compounds are consumed during drinking, showering, bathing, and swimming through three routes: ingestion, contact with skin, and inhalation (Iszatt, 2011 So the main objective of the present study aims to investigate the concentration of THMs and its groups in ASWP and its distribution systems and comparing it seasonally and also investigate some microbiological activities that have a direct effects on water quality, and consequently the human health.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine is an oxidizing agent that reacts rapidly with organic and inorganic matter present in water (WHO, 1996). Unfortunately, natural organic matter (NOM) in water reacts with chlorine to form THMs as disinfection byproducts (D-BPs) (Zimoch, 2014). However, the presence of THMs in chlorinated drinking water and their lifetime exposure on humans have raised a great concern due to its carcinogenicity and recognition as potential risk to human health (Zimoch, 2010).These compounds are consumed during drinking, showering, bathing, and swimming through three routes: ingestion, contact with skin, and inhalation (Iszatt, 2011 So the main objective of the present study aims to investigate the concentration of THMs and its groups in ASWP and its distribution systems and comparing it seasonally and also investigate some microbiological activities that have a direct effects on water quality, and consequently the human health.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, after 1990 there was a sharp increase in the length of pipes' of exploited systems -from about 93 thousands km in 1990 to about 273 thousand km in 2010. Both these factors resulted in elongation of the time of water transport from the point of intake to the receiver [15,16], with all its negative results as the following: precipitation of sludge [17,18], microbiological risks [19,20] or intensification of pipes' material impact on the transferred water quality [21][22][23][24]. Research conducted in Poland confirmed exceeding many factors of pollution in the water transported by water supply systems as a result of secondary contamination.…”
Section: Introductionmentioning
confidence: 90%
“…According to the Polish regulation, the sum of the mass concentrations of chloroform, bromodichloromethane, dibromochloromethane, and bromoform has to be below 100 μg/L in drinking water [16]. THMs are consumed during drinking, showering, bathing, and swimming through three routes: ingestion, contact with skin, and inhalation [3][4][5][6][7][8][9][10]14,17].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, natural organic matter (NOM) in water reacts with chlorine to form THMs as disinfection by-products (DBPs). THMs constitute the major category of DBPs [3,4]. Chloroform (CHCl 3 ), bromoform (CHBr 3 ), bromodichloromethane (CHCl 2 Br), and dibromochloromethane (CHClBr 2 ) are the four compounds belonging to the group of THMs [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation